Penerapan TaRL pada Hasil Belajar PJOK Senam Anak Indonesia Hebat di SMP Lab Unesa 3 - Febri Lian Putra; Ferdi Dwi Alvianto; Sigra Santika Satria Dhani; Abdul Rachman Syam Tuasikal (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
This study aims to describe the effect of implementing Teaching at the Right Level (TaRL) on improving Physical Education (PJOK) learning outcomes for students. This research is a Classroom Action Research (CAR) with a design model based on Kurt Lewin's opinion, which consists of four stages: Planning, Acting, Observing, and Reflecting. The research subjects were 40 seventh-grade students of SMP Labschool Unesa 3 in the 2024/2025 academic year. The data collection instrument used in this study was a learning outcome test on the Indonesian Children's Gymnastics Practice Material. This research was conducted over two cycles, each consisting of two meetings and one assessment, which consisted of four stages: planning, action, reflection, and evaluation, from late April to mid-May 2025. Data were analyzed at each cycle, and percentage analysis was performed. The learning outcomes in the first cycle showed that 54% of students achieved mastery, with an average score of 73.19. An improvement was seen in the second cycle, with 80% of students achieving mastery, with an average score of 80.11. Based on the results of this study, it can be concluded that the implementation of Teaching at the Right Level (TaRL) can improve the learning outcomes of seventh-grade students of SMP Labschool Unesa 3 in the Indonesian Children's Gymnastics Practice Material.